Mesenteric panniculitis: Case report - Ekuke, Eddy Oleko; Diallo, Fatoumata Djouldé; Benjelloun, El Bachir; Dafr-Allah, Benajah (Journal of Surgery and Medicine, 2018)
Rare and poorly documented, mesenteric panniculitis (MP) is characterized by nonspecific inflammation affecting adipose tissue of the mesentery. Modern imaging, computed tomography and especially magnetic resonance imaging can be very useful in the workup thus reducing unnecessary laparotomy hitherto required for the positive diagnosis of this affection. Pathology examination still remains necessary as it eliminates key differentials notably liposarcoma. This could be achieved through imaging-guided biopsy. We hereby report a case of sclerosing mesenteritis in a 43 years old patient.